Efektivitas Biopestisida Menggunakan Fermentasi Daun Pepaya (Carica papaya) untuk Mengurangi Tingkat Kerusakan Daun pada Tanaman Jagung Manis (Zea mays L. saccharata) - ADE, ADE NUR KURNIAWAN; Sudiarti, Diah; Bukhori Muslim, Imam (Universitas Islam Jember, 2021)
ABSTRACT Biopesticides are natural pesticides that come from nature such as leaves, roots, stems, and fruit. This research is about the efectiviness of papaya (Carica papaya) biopesticide with cow urine fermentation in sweet corn (Zea mays L. saccharata), which was conducted in Glagahwero Kalisat, Jl. Mayangan, Desa Glagahwero, Kec. Kalisat, Kab. Jember this study aims to determine the effectiviness of biopesticides on sweet corn (Zea mays L.saccharata). This type of research is experimental. The procedure used was a Completely Randomized Design (CRD). Based on the results of research, the effectiviness of biopesticides using papaya leaf fermentation is not effective due to several factors, namely the season is not right, the planting area is not right, the plant layout is not good, grasshopper pests are difficult to control. Keywords : Plant Papaya (Carica papaya), Plant Sweet Corn (Zea mays L. saccharta)